(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Clarithromycin resistance globally has challenged the success of conventional Clarithromycin based triple therapy for Helicobacter Pylori eradication. Levofloxacin has primarily been considered as a second-line treatment but may also be used as primary therapy. Recently, some studies have evaluated its efficacy as a valid alternative to standard antibiotics as first-line therapy for H. pylori infection. This study was intended to assess the eradication success of Levofloxacin based first-line triple therapy and also to see it’s compliance & adverse effect profile. Materials and methods: This non-randomized single-arm clinical trial was carried out in the Department of Gastroenterology, BSMMU from March 2016 to March 2017 involving 123 H. pylori-positive patients with endoscopically proven peptic ulcer disease to assess the eradication success of levofloxacin based first-line triple therapy and also to see its compliance and adverse effect profile. H. pylori status were detected by urea breath test. Patients were treated with amoxycillin 1 gm 12 hourly, levofloxacin 500 mg 12 hourly and omeprazole 20 mg 12 hourly for 14 days and were followed-up at 2 months after completion of therapy for repeat urea breath test. Results: A total of 97 patients returned for followup. Male proportion was 63.41% and female was 36.58% with the median age of 57 years. On intention-to-treat analysis, the eradication rate of H. pylori was 65.85% and on per-protocol analysis, it was 83.50%. Total 15.44% patients developed adverse effects, all were mild to moderate in nature. One patient discontinued treatment because of epigastric pain and vomiting. Conclusion: Levofloxacin-based therapy was effective, well-tolerated and compliance was excellent; but the eradication rate was not satisfactory. JCMCTA 2020 ; 31 (1) : 102-107